A Polarizing Issue: Faculty and Staff Perceptions of Intercollegiate Athletic Academics, Governance, and Finance Post-NCAA Investigation - Gregory Lewinter; Erianne A. Weight; Barbara Osborne; John Brunner (Journal of Applied Sports Management, 2013)
Following an athletics scandal that invoked internal upheaval and National Collegiate Athletic Association (NCAA) sanctions, non-athletics employees at The University of North Carolina at Chapel Hill were invited to participate in a survey investigating their satisfaction with academics, governance, and finance of intercollegiate athletics. This study extends the 2006 Knight Commission sponsored study, Faculty Perceptions of Intercollegiate Athletics: A National Study of Faculty at NCAA Division I Football Bowl Subdivision (FBS) Institution to a post-infraction single-school population. Three philosophical viewpoints describing basic faculty issues and assumptions that divide Division I institutional reformers were utilized to frame the examination (Sack, 2009). Results indicate polarized viewpoints on most issues with satisfaction for athletics positively correlated with event attendance. Reflecting this polarization, respondent narratives demonstrated vast array of responses from individuals with no concern regarding current practices to individuals calling for athletics to be removed from the university.
Keywords: NCAA; College Sport; Reform; Faculty Governance; Intercollegiate Athletics Administration